Ethyl cellulose-chitosan microspheres of sumatriptan succinate for nasal drug delivery - Salah Abdul Mahdi Alghareeb; Adebisi O Adeola (University of Huddersfield Press, 2023)
The research investigated the preparation of mucoadhesive microspheres using ethyl cellulose and chitosan as polymers. Two methods were employed, with the first method utilizing an emulsion solvent evaporation technique and the second method incorporating additional homogenization and sonication steps. The results showed that the first method yielded nearly perfect spherical microspheres with a particle size range of 50 µm, while the second method produced irregularly shaped microspheres with larger particle sizes within the range of 200 µm. The drug entrapment efficiency was significantly higher in the first method compared to the second method, and within the first method, drug entrapment efficiency decreased with increasing chitosan concentration. These findings underscore the importance of method selection and chitosan concentration in microsphere synthesis, providing insights for optimizing drug delivery systems for targeted applications.